Sistem Pengolahan Sampah Pasar Menjadi Kompos dengan Metode Takakura di Pasar Alai Padang - Darwel Darwel; Lindawati Lindawati; Aidil Onasis; Awalia Gusti (Poltekkes Kemenkes Padang, 2020)
The market is one of the waste-producing places which, if not transported every day, will become a source of disease. The amount of organic waste produced can be processed into compost using a takakura basket. The purpose of this study is to determine the level of knowledge of traders in processing market waste. This type of research is descriptive in which the object under study is organic waste consisting of fruits and vegetables. Data analysis was performed using a table describing the average volume of waste produced per trader every day as well as the level of knowledge of traders on processing market waste into compost. The results of the analysis showed that most traders (52.9%) had high knowledge about organic waste processing. The average weight of organic waste produced by traders at Alai Padang Market is 9.18 kg per day and composting time is 30 days. Trash produced by traders can be processed using the takakura method, where the weight reduction effectiveness is more than 80%. It is hoped that Market Managers will always provide directions to traders so that they can process the generated waste first before dumping it into the TPS using the takakura method. It is also hoped that traders will always improve their knowledge in processing the waste produced so that the resulting waste can be of economic value.